Model Dependent Controller for Underwater Vehicle - Wesam M. Jasim (UHD Journal of Science and Technology, 2017)
In this work, a model dependent control design method based feedback scheme was investigated for autonomous underwater vehicle control. The controller was designed with the nonlinear terms - inertia, hydrodynamic damping, and gravitational, and buoyancy - of the vehicle dynamical model consideration. Then, the model independent controller (PD) was also investigated, with no nonlinear terms consideration. The stability analysis of the proposed model dependent feedback controller was obtained based on a Lyapunov function. The simulation results of the proposed controller were compared with that of PD controller. The comparison shows the validation of the proposed controller.